2013
DOI: 10.3797/scipharm.1209-12
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gradient Stability-Indicating Reversed-Phase LC Method for the Estimation of Impurities in Omeprazole and Domperidone Capsules

Abstract: A gradient reversed-phase liquid chromatographic (RP-LC) method was developed for the quantitative estimation of impurities in the pharmaceutical dosage form of Omeprazole and Domperidone capsules. The developed method is a stability-indicating test method for the estimation of impurities generated during the formulation and storage of Omeprazole and Domperidone capsules. The chromatographic separation was achieved on a column packed with octadecyl silane, having a column length of 250 mm and diameter of 4.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Для образования активных метаболитов, что требует последовательного протонирования в начале пиридинового, а затем бензимидазольного колец, оптимальным является постепенное снижение рН от среднекислых к сильнокислым значениям, что в просвете желудка маловероятно. Даже если в желудке образуются активные метаболиты, их свой ством является быстрое образование дисульфидных мостиков с остатками цистеина белков, ими обладаю щих, и такое связывание исключает продвижение по ЖКТ активированных ИПП и, соответственно, их абсорбцию [27][28][29]. Поэтому для обеспечения всасывания ИПП их лекарственные формы защищают кишечнорастворимыми полимерными оболочками.…”
Section: федеunclassified
“…Для образования активных метаболитов, что требует последовательного протонирования в начале пиридинового, а затем бензимидазольного колец, оптимальным является постепенное снижение рН от среднекислых к сильнокислым значениям, что в просвете желудка маловероятно. Даже если в желудке образуются активные метаболиты, их свой ством является быстрое образование дисульфидных мостиков с остатками цистеина белков, ими обладаю щих, и такое связывание исключает продвижение по ЖКТ активированных ИПП и, соответственно, их абсорбцию [27][28][29]. Поэтому для обеспечения всасывания ИПП их лекарственные формы защищают кишечнорастворимыми полимерными оболочками.…”
Section: федеunclassified
“…The conditions developed in this 2D-LC approach can be considered more or less generic for detection of impurities in APIs, at least when eluting under reversed phase LC conditions. In this robust and method, good finds were also achieved for analyses of metoclopramide, acetaminophen, diclofenac, ibuprofen, and lidocaine [32][33][34][53][54][55][56].…”
Section: Multi-dimensional Lc Analysis In Pharmaceutical Products (Tr...mentioning
confidence: 99%
“…An extensive literature survey found that a number of analytical methods have been reported in the literature for the individual determination of KET or OMZ. These methods include HPLC estimation (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), UV spectrophotometry (21)(22)(23) and LC-MS estimation (24)(25)(26). The simultaneous assay determination of KET and OMZ in capsules was also reported (27).…”
Section: Introductionmentioning
confidence: 99%